Ultrahigh-strength spring steel for automobile hydraulic torque converter and manufacturing method thereof

By adopting spring steel for automotive torque converters with specific chemical components and carrying out fine smelting and heat treatment processes, the problem that spring steel in the prior art cannot meet the requirements of high impact and high fatigue performance is solved, and the steel wire can penetrate at high temperature The performance stability and ultra-high stress design requirements after nitrogen treatment.

CN119464925AInactive Publication Date: 2025-02-18JIANGYIN XINGCHENG GOLD MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411288653.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot provide spring steel that meets the requirements of high impact and high fatigue performance of springs for automotive torque converters, and the hardness of the steel wire is greatly reduced after high temperature nitriding treatment.

Method used

Spring steel for automotive torque converters composed of specific chemical components, including C, Si, Mn, Cr, V, Mo and other elements. Through fine smelting and heat treatment processes, the steel wire is nitrided at 400-500℃. The hardness is reduced after ≤1.0HRC.

Benefits of technology

The tensile strength of the steel wire reaches 2000-2200MPa, the surface shrinkage rate is ≥40%, and the fatigue life is ≥6 million times. It meets the ultra-high stress design requirements of the springs for automobile torque converters, and ensures that the steel wire is nitriding after high temperature nitriding. Stable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464925A_ABST
    Figure CN119464925A_ABST
Patent Text Reader

Abstract

The invention relates to ultrahigh-strength spring steel for an automobile hydraulic torque converter. The ultrahigh-strength spring steel comprises, by mass, 0.55%-0.70% of C, 1.60%-2.20% of Si, 0.30%-0.80% of Mn, 0.60%-1.00% of Cr, 0.10%-0.30% of V, 0.05%-0.30% of Mo, smaller than or equal to 0.020% of P, smaller than or equal to 0.020% of S, smaller than or equal to 0.0010% of Al, smaller than or equal to 0.0010% of Ti, smaller than or equal to 0.10% of Cu, smaller than or equal to 0.30% of Ni, smaller than or equal to 0.15% of Nb, smaller than or equal to 0.00005% of H, smaller than or equal to 0.008% of N, 0.0007%-0.0025% of O and the balance And the balance of Fe and inevitable impurities. The tensile strength of the ultra-high-strength spring steel for the hydraulic torque converter of the automobile is 2000-2200 MPa, the steel type has good anti-tempering stability while meeting good fatigue performance and impact resistance, after a heat treatment steel wire is rolled into a spring, the steel wire hardness can be reduced to be smaller than or equal to 1.0 HRC after nitriding treatment is conducted for 5-8 hours at the temperature of 400-500 DEG C, and the steel wire hardness can be reduced to be smaller than or equal to 1.0 HRC after nitriding treatment is conducted for 5-8 hours at the temperature of 400-500 DEG C; the ultrahigh stress design requirement of the spring steel for the automobile hydraulic torque converter can be met, and the steel wire for the spring is not limited to a round shape and can be made into an oval shape, an oval shape and other special shapes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special steel smelting, and specifically relates to an ultra-high strength spring steel for automobile hydraulic torque converter and a manufacturing method thereof. Background Art

[0002] The torque converter is an important component of the power transmission system of fuel vehicles and the power transmission system of new energy vehicles. The hydraulic automatic transmission has always been a weak point in the development of my country's independent automobile brands. After the automobile torque converter uses a spring, it can avoid or weaken the impact caused by the high speed of the engine, making the power transmission of the engine more stable, which can significantly promote the smooth start of the car, rapid or gentle acceleration, and can greatly extend the life of the automobile power transmission system and improve driving safety.

[0003] In order to meet the needs of high impact and high fatigue performance of automotive torque converters, the cross-sectional area of ​​the spring steel wire is equivalent to 7-20 square millimeters, the tensile strength is 2000-2200MPa, the surface reduction rate is ≥40%, and the fatigue life is ≥6 million times. The surface of the spring steel wire needs to be nitrided. After nitriding for 5-8 hours at 400-500℃, the hardness of the steel wire is reduced by ≤1.0HRC.

[0004] The currently commonly used spring steel materials cannot meet the requirements of springs for torque converters. Therefore, the present invention aims to provide a spring steel for automobile torque converters having good anti-tempering stability and a steel wire tensile strength of 2000-2200MPa, while meeting the high impact and high fatigue performance of the spring and a manufacturing method thereof. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a spring steel for an automobile torque converter and a manufacturing method thereof in view of the above-mentioned prior art. The steel has good fatigue performance and good tempering resistance stability. After the heat-treated steel wire is rolled into a spring, it can meet the requirements of nitriding for 5-8 hours at a temperature of 400-500°C, and the hardness of the steel wire is reduced by ≤1.0HRC, which can meet the ultra-high stress design requirements of the spring steel for the automobile torque converter. The shape of the spring steel wire is not limited to a circle, and can be made into an oval, elliptical and other special shapes.

[0006] The technical solution adopted by the present invention to solve the above-mentioned problem is: a spring steel for an ultra-high strength automobile torque converter, wherein the chemical composition and the mass percentage of the steel are: C: 0.55-0.70%, Si: 1.60-2.20%, Mn: 0.30-0.80%, Cr: 0.60-1.00%, V: 0.10-0.30%, Mo: 0.05-0.30%, Ni: ≤0.25%, Al: ≤0.0008%, Nb: ≤0.04%, P: ≤0.020%, S: ≤0.020%, Cu: ≤0.10%, N: ≤0.008%, Ti≤0.0012%, O: 0.0007%-0.0020%, S: ≤0.020%, H: ≤0.00005%, and the balance is Fe and unavoidable impurities.

[0007] The design principles of the chemical elements of the spring steel for automobile torque converter of the present invention are as follows: C is the most important strengthening element in spring steel for torque converters. It has two functions. On the one hand, it dissolves in the steel to form a solid solution, forming an interstitial solid solution strengthening effect; on the other hand, it combines with strong carbide-forming elements to form carbides, forming a precipitation strengthening effect. When the C content is less than 0.55%, the strength requirements of the spring steel cannot be met, and at the same time, it cannot meet the formation of second-phase carbonitrides with microalloying elements. However, when the C content is greater than 0.70%, large pieces of carbides are formed in the spring steel, reducing the plastic toughness of the steel. Therefore, the C content of the spring steel for automobile torque converters in the present invention is 0.55-0.70%.

[0008] Si has a strong solid solution strengthening effect, which can significantly improve the elastic limit, yield limit and yield strength ratio of steel, so that the spring has higher strength and better resistance to elastic decay. Si is also a deoxidizer and reducing agent in the steelmaking process, which can reduce the oxygen content in the steel and improve the fatigue life of the spring. Therefore, the Si element content of the spring steel for automobile hydraulic torque converter in the present invention is 1.30-2.00%.

[0009] Mn dissolved in the matrix has a solid solution strengthening effect, which can effectively improve the matrix strength and anti-elasticity. However, manganese has the effect of promoting grain growth, so manganese is more sensitive to overheating, so the Mn content of the spring steel for automobile hydraulic torque converter cannot be too high. Therefore, the Mn element content of the spring steel for automobile hydraulic torque converter in the present invention is 0.30-0.80%.

[0010] Cr can improve the tensile strength, hardness, yield strength and elastic decay resistance of spring steel. Since Cr is a weak carbide-forming element, appropriate addition of Cr can make carbides evenly distributed in the steel matrix. When more Cr is added, large pieces of carbides are formed. Therefore, the Cr element content of the spring steel for automobile torque converter in the present invention is 0.30-0.80%.

[0011] V is a strong carbide-forming element, which can form a precipitation strengthening effect, significantly improve the strength of steel without reducing plasticity. Vanadium carbide can effectively organize grain growth, refine grains, improve strength and toughness, and can also improve the spring's resistance to elastic attenuation and hydrogen embrittlement sensitivity. Therefore, the V content of the spring steel for automobile hydraulic torque converter in the present invention is: 0.10-0.30%.

[0012] Mo: Molybdenum can improve the tensile strength and elastic limit of spring steel, improve the tempering stability of martensite, reduce the hardness reduction range of spring during nitrogen infiltration, and can greatly improve hardenability, refine grains, and improve toughness when combined with Cr and Ni; reduce temper brittleness, and increase strength without reducing plasticity. Therefore, the Mo element content of the spring steel for automobile hydraulic torque converter in the present invention is: 0.05-0.30%.

[0013] Al is a strong deoxidizing element and has a certain grain refining effect, but the brittle Al2O3 inclusions formed have a fatal effect on the fatigue life of the spring steel. Therefore, the Al element content of the spring steel for the automobile torque converter in the present invention is ≤0.0010%.

[0014] Ti is also a strong deoxidizing element and has a good grain refining effect, but forms TiN-type inclusions with high hardness with N, which has a great influence on the fatigue life of the spring steel. Therefore, the Ti element content of the spring steel for the automobile torque converter in the present invention is ≤0.0010%.

[0015] The Cu element tends to gather at the grain boundaries, which easily leads to hot brittleness and affects the toughness of the spring steel for automobile hydraulic torque converter. Therefore, the Cu element content of the spring steel for automobile hydraulic torque converter in the present invention is ≤0.10%.

[0016] Nb is a carbonitride forming element, which can increase the precipitation nucleation rate of carbonitrides during tempering, prevent the growth of grains and form refined grains, and improve the strength of steel wire. Therefore, the Nb element content of the spring steel for automobile torque converter in the present invention is ≤0.15%.

[0017] N is a nitrogen compound forming element, and the carbonitride formed by combining with V and Nb improves the matrix strength and refines the structure. However, too high a N content will produce coarse carbonitrides. Therefore, the N content of the spring steel for the automotive torque converter in the present invention is ≤0.008%.

[0018] Too high H content will cause white spots, spot segregation and hydrogen-induced delayed fracture, so the H content of the spring steel for automobile torque converter in the present invention is ≤0.00005%.

[0019] The O content represents the number of inclusions in the steel. Reducing the oxygen content in the steel is beneficial to improving the fatigue life of the spring steel. Therefore, the O content of the spring steel for the automobile torque converter in the present invention is 0.0007%-0.0025%.

[0020] The matrix structure of the spring steel for automobile hydraulic torque converter of the present invention is tempered troostite+troostite, and the matrix structure contains a second phase of vanadium, niobium and molybdenum carbonitride, and the size of the second phase is 8-80nm.

[0021] The austenite grain size of the spring steel for the automobile hydraulic torque converter of the present invention reaches 11-15 levels.

[0022] The spring steel for automobile hydraulic torque converter of the present invention has a strength of 2000-2200 MPa and an area reduction ratio of ≥40%, which can meet the requirements of the spring steel for automobile hydraulic torque converter for high strength and high toughness.

[0023] The spring steel for the automobile hydraulic torque converter of the present invention has a fatigue life of the spring of ≥6 million times, which can meet the requirement of the spring steel for the automobile hydraulic torque converter for ultra-high fatigue life.

[0024] Another object of the present application is to provide a method for manufacturing ultra-high strength spring steel for automobile torque converter, the main steps of which are as follows: (1) Use molten iron pretreatment to remove sulfur from the molten iron. After molten iron pretreatment, the sulfur content is ≤0.005%, which can make the sulfur content in the finished steel ≤0.005%. High sulfur content is not good for the fatigue life of spring steel for automotive torque converters. MnS inclusions are distributed along the rolling direction of the steel wire and are easy to become fatigue sources.

[0025] (2) Rough refining is carried out by using a converter or electric furnace. The S content of the molten iron entering the rough refining furnace is ≤0.005%. Scrap steel produced in-house is used to reduce the introduction of harmful elements, especially the five harmful elements As, Sb, Sn, Pb, and Bi. The content of the five harmful elements in the finished steel is ≤0.0030%. The five harmful elements affect the plasticity and tempering stability of the steel. The rough refining furnace controls the oxygen content in the steel and increases the final C content. The P content in the steel is ≤0.012% and the S content is ≤0.005% when the steel is tapped. High-grade alloys are added during tapping to reduce the introduction of harmful elements such as P, S, Ti, and Al.

[0026] (3) After rough refining, the molten steel enters the ladle refining furnace. The basicity of the refining slag in the ladle refining furnace is less than or equal to 1.4 (the mass percentage of CaO content and SiO2 content in the refining slag). The use of weakly alkaline slag can remove brittle inclusions in the steel and reduce Ds-type inclusions that are fatal to fatigue life. The inclusions remaining in the steel have the ability to deform during rolling, that is, to form plastic inclusions. Because plastic inclusions can be plastically deformed during rolling and drawing, the size of the inclusions is reduced, achieving the purpose of harmless inclusions. The smaller the size of the inclusions, the more beneficial it is to improve the fatigue life of the spring; use vacuum treatment RH or VD furnace to remove harmful gases N, H, O in the steel, so that the N content in the steel is ≤0.0050%, the O content is ≤0.0017%, and the H content is ≤0.0001%. High N content affects the plasticity of the spring steel and reduces the impact toughness of the spring; H is fatal to ultra-high strength steel and is more likely to produce hydrogen-induced delayed fracture; the higher the O content, the more inclusions there will be in the steel, which is not conducive to the fatigue life of the spring.

[0027] (4) Refining qualified molten steel, ensuring that inclusions fully float up, the temperature of the molten steel is suitable for pouring, using protective pouring during pouring, reducing contact with air, and reducing the molten steel from absorbing nitrogen and oxygen and affecting the quality of the molten steel. The superheat of the molten steel entering the tundish is ≤25℃. Under the condition of ensuring pouring, the lower the superheat, the better, which is conducive to controlling the uniformity of the ingot structure and reducing the harm caused by segregation. When the continuous casting solid phase ratio is 0.63-0.75, use the end to gently press down, the pressing amount is 2.1-3.6% of the ingot thickness, which can make the center segregation of the ingot ≤1.0 level, the center looseness ≤1.0 level, the center carbon segregation index ≤1.3, and finally make the deviation of the tensile strength of different steel wires ≤50Mpa. The cross-sectional dimensions of the steel billet cast by the continuous casting machine are: length 200-500mm, width 200-550mm.

[0028] (5) Qualified continuous casting billets enter the continuous heating furnace, and the temperature of the billets is controlled to be ≥400℃. According to the calculation and summary of the alloy elements and second phase solid solution of this steel type, the heating temperature is determined to be 1120-1230℃. The total heating time is controlled during heating. The heating time varies according to the billet type, but the total heating time must ensure that the micro-alloying element carbonitride is fully integrated into the austenite, that is, the total heating time is 2.5min / mm-3.5min / mm (mm is the cross-sectional size of the billet). After the billet is fully heated, the rolling deformation can be completely penetrated into the core, and the defects such as looseness, shrinkage, and microcracks in the core can be welded to reduce the center segregation and organizational differences. The cross-sectional size of the rolling intermediate billet is: the square billet is 140mm-220mm long and 140mm-220mm wide, and the diameter of the round billet is 140mm-220mm.

[0029] (6) After the casting is rolled, there are pits, folds, cracks, scratches and other defects on the surface of the intermediate billet that affect the surface quality of the steel wire. First, use magnetic powder or infrared flaw detection to determine the defect location and mark it, and then grind and clean the defect at the marked location. For intermediate billets without surface defects, use grinding wheels and other equipment to completely remove the surface layer within 1-2 mm near the surface of the intermediate billet to remove the surface decarburization layer. Because process (7) further deepens the decarburization of the intermediate billet, the surface decarburization of the finished wire rod increases, which reduces the surface hardness and causes early fatigue failure of the spring.

[0030] (7) The intermediate billet with the surface decarburized layer and defects removed enters the heating furnace. In order to control and achieve the target of 11-15 austenite grain size of the finished steel wire, the heating time should be less than 2 hours and the heating temperature should be 950-1150℃.

[0031] (8) After the intermediate billet comes out of the heating furnace, it is immediately dephosphorized with high-pressure water to remove the surface oxide layer and defects during the heating process. According to the thermoplasticity and thermal simulation data of the steel grade, the starting rolling temperature is greater than 890°C, the process rolling temperature is 890-1050°C, and the wire drawing temperature is 830-900°C. Since the steel contains more alloy elements and the size of the wire rod is small, it is easy to produce abnormal martensite or bainite structure. In order to make the wire rod obtain the sorbite structure that is conducive to drawing, the cooling rate of the wire rod is 3.0-5.5°C / s.

[0032] (9) The wire rod is drawn in multiple passes to form the steel wire. In order to further increase the grain size of the steel wire and reduce surface defects, the wire rod is drawn to the size of the finished steel wire, and the total surface reduction rate is ≥65%.

[0033] (10) The steel wire needs to be heat treated after drawing. The steel wire is heat treated while being heated, that is, the online heat treatment method is adopted. According to the austenitizing temperature of the steel, the heating temperature before quenching is 860-980℃. The quenching medium is water or oil. When the quenching medium is water, the temperature needs to be controlled at 20-50℃. When oil is used, the temperature is ≤40℃. The tempering temperature is selected at 420-500℃ according to the requirements of the spring for the tensile strength of the steel wire. The lower the tempering temperature, the higher the tensile strength. Before the steel wire is coiled, the surface defects are detected by flaw detection equipment. If the depth of the surface defects is greater than 0.1mm, the color code needs to be sprayed.

[0034] Compared with the prior art, the advantages of the present invention are: The spring steel for automobile hydraulic torque converter of the present invention has a tensile strength of 2000-2200MPa, a surface reduction rate of ≥40%, a fatigue life of the spring of ≥6 million times, and can meet the requirement that after nitriding at 400-500°C for 5-8 hours, the hardness of the steel wire is reduced by ≤1.0HRC, and can meet the ultra-high stress design requirement of the spring steel for ultra-high strength automobile hydraulic torque converter. The shape of the spring steel wire is not limited to a circle, and can be made into an oval, elliptical or other special shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a physical picture of the product of Example 1 of the present invention.

[0036] Figure 2 This is a physical picture of the product of Example 2 of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is described in more detail in conjunction with the preferred embodiments of the present invention. However, these embodiments are only descriptions of the preferred implementation methods of the present invention and cannot impose any limitation on the scope of the present invention.

[0038] Example 1: The production method of ultra-high strength spring steel for automobile torque converter is as follows: the molten iron temperature is 1320°C, the P content in the molten iron is 0.095%, the S content is 0.043%, the molten iron is pretreated by the KR method in the ladle, the molten iron temperature after S removal is 1238°C, the P and S contents are 0.093% and 0.005% respectively, and the rest is Fe and unavoidable impurities.

[0039] The converter is used for smelting. The temperature of the molten steel is 1626℃ when tapping, the C content is 0.18%, the P content is 0.008%, and the S content is 0.004%. High-quality alloy and carbon powder are used when tapping. The LF refining furnace uses Ar gas to stir and accompany the entire smelting process. 945kg of refined slag is added. The basicity of the refined slag is 1.25, that is, the ratio of the CaO percentage content to the SiO2 percentage content is 1.25. After the refining and smelting is completed, all the alloy elements that need to be added reach the target value. The RH furnace is used for vacuum treatment. The vacuum degree is 0.5tor and maintained for 21 minutes. At the end of the vacuum, the H content is 0.00006%, the O content is 0.0012%, and the N content is 0.0036%. After the vacuum ends, Ar gas is continued to be blown for 11 minutes before continuous casting.

[0040] During continuous casting, argon protection is used throughout the entire process to reduce contact with air. The chemical composition N content of the continuous casting tundish is monitored to be 0.0042%, the tundish overheat is 23°C, the cross-sectional size of the crystallizer is 390*510mm, and the size of the ingot after light pressing is 382*509mm.

[0041] The surface temperature of the continuous casting billet was measured to be 493°C before entering the heating furnace. The highest heating temperature of the billet was 1172°C and it was kept warm for 220 minutes. The cross-sectional size of the rolling intermediate billet was 160*160mm.

[0042] The intermediate billet was inspected by magnetic particle inspection, and the defects found were manually ground. The total decarburization depth of the intermediate billet was 1.12mm. The surface decarburization layer was cleaned with a grinding wheel, and the grinding depth was 1.3mm.

[0043] The surface-grinded intermediate billet enters the heating furnace, with the highest heating temperature of 1120℃ and heat preservation for 103min, the starting rolling temperature of 1012℃, the wire rod spinning temperature of 960℃, and the rolled wire rod specification of φ7.5mm. All Stelmor fans are turned off, the cooling rate is 3.7℃ / s, and the wire rod structure is inspected to have a sorbitization rate of 92%.

[0044] The wire rod was pickled and saponified, and the φ7.5mm was drawn to φ4.2mm steel wire through 7 passes. The drawn steel wire was aged for 5 days and then heat treated. The highest heating temperature before quenching was 923℃ and kept warm for 43s. It was quenched in water at 35℃ and then tempered at 432℃. Eddy current flaw detection was used before winding, and the flaw detection accuracy was 0.1mm. There were 732kg of steel wire, of which 3 color codes were defective. The mechanical properties of the steel wire were tested, with a tensile strength of 2063MPa and a surface reduction of 43%. The hardness at half the radius of the steel wire was 55.6HRC. The steel wire was used to make a spring for a hydraulic torque converter. After nitriding at 435℃ for 5 hours, the hardness at half the radius of the steel wire was tested again, and it was 54.6HRC. This batch of springs has been fatigue-tested for 6 million times without any breakage or cracks, indicating that the steel wire can meet the fatigue life requirements of the spring. The tensile strength is 2060MPa and the surface reduction is 43%.

[0045] Example 2: The production method of ultra-high strength spring steel for automobile torque converter, the molten iron temperature is 1293℃, the P content in the molten iron is 0.102%, the S content is 0.039%, the molten iron is pretreated by KR method in the ladle, the molten iron temperature after S removal is: 1226℃, the P and S contents are 0.103% and 0.004% respectively, and the rest is Fe and unavoidable impurities.

[0046] Electric furnace smelting is used, and the molten steel temperature is 1639℃ when tapping, the C content is 0.09%, the P content is 0.010%, and the S content is 0.005%. High-quality alloy and carbon powder are used when tapping. The LF refining furnace uses Ar gas to stir and accompany the entire smelting process. 923kg of refined slag is added, and the basicity of the refined slag is 1.25, that is, the ratio of the CaO percentage content to the SiO2 percentage content is 1.25. After the refining and smelting is completed, all the alloy elements that need to be added reach the target value. VD furnace is used for vacuum treatment, and the vacuum degree is 133Pa and maintained for 21 minutes. At the end of the vacuum, the H content is 0.0009%, the O content is 0.0014%, and the N content is 0.0045%. After the vacuum ends, Ar gas is continued to be blown for 18 minutes before continuous casting.

[0047] During continuous casting, argon protection is used throughout the entire process to reduce contact with air. The chemical composition N content of the continuous casting tundish is monitored to be 0.0049%, the tundish overheat is 21°C, the cross-sectional size of the crystallizer is 300*340mm, and the size of the ingot after light pressing is 291*341mm.

[0048] The surface temperature of the continuous casting billet was measured to be 521°C before entering the heating furnace. The highest heating temperature of the billet was 1172°C and it was kept warm for 190 minutes. The cross-sectional size of the rolling intermediate billet was 150*150mm.

[0049] The intermediate billet is inspected by infrared and the defects found are manually ground. The total decarburization depth of the intermediate billet is 1.02mm. The surface decarburization layer is cleaned with a grinding wheel and the grinding depth is 1.3mm.

[0050] The surface-grinded intermediate billet enters the heating furnace, with the highest heating temperature of 1180℃ and heat preservation for 100min, the starting rolling temperature of 1010℃, the wire rod spinning temperature of 958℃, and the rolled wire rod specification of φ9mm. All Stelmor fans are turned off, the cooling rate is 3.3℃ / s, and the wire rod structure is inspected to have a sorbitization rate of 91%.

[0051] The wire rod was pickled and saponified, and the φ9mm was drawn to φ4.8mm steel wire through 7 passes. The drawn steel wire was aged for 5 days and then heat treated. The maximum heating temperature before quenching was 923℃ and kept warm for 51s. Oil was used as the quenching medium, and then tempered at 428℃. Eddy current flaw detection was used before winding, and the flaw detection accuracy was 0.1mm. There were 652kg of steel wire, of which 2 color codes were defective. The mechanical properties of the steel wire were tested, with a tensile strength of 2043MPa and a surface reduction of 42%. The hardness at half the radius of the steel wire was 55.3HRC. The steel wire was used to make a spring for a hydraulic torque converter. After nitriding at 435℃ for 5 hours, the hardness at half the radius of the steel wire was tested again, and it was 54.4HRC. This batch of springs has been fatigue tested for 6 million times without any breakage or cracks, indicating that the steel wire can meet the fatigue life requirements of the spring.

[0052] Although the preferred embodiments of the present invention are described in detail above, it should be clearly understood that various modifications and variations are possible for those skilled in the art. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ultra-high strength spring steel for automobile torque converter, characterized in that: The chemical composition of the spring steel and its mass percentage are: C: 0.55-0.70%, Si: 1.60-2.20%, Mn: 0.30-0.80%, Cr: 0.60-1.00%, V: 0.10-0.30%, Mo: 0.05-0.30%, Ni: ≤0.25%, Al: ≤0.0008%, Nb: ≤0.04%, P: ≤0.020%, S: ≤0.020%, Cu: ≤0.10%, N: ≤0.008%, Ti≤0.0012%, O: 0.0007%-0.0020%, S: ≤0.020%, H: ≤0.00005%, and the balance is Fe and unavoidable impurities.

2. The ultra-high strength spring steel for automobile torque converter according to claim 1, characterized in that: The matrix structure of the spring steel is tempered troostite+troostite, the matrix structure contains a second phase of vanadium, niobium and molybdenum carbonitride, the size of which is 8-80nm, and the austenite grain size reaches 11-15 levels.

3. The ultra-high strength spring steel for automobile torque converter according to claim 1, characterized in that: The tensile strength of the spring steel is 2000-2200 MPa, the area reduction rate is ≥40%, and the fatigue life of the spring is ≥6 million times.

4. A method for manufacturing the ultra-high strength spring steel for automobile torque converter according to claim 1, characterized in that: The process flow of the method is as follows: (1) pretreatment of molten iron; (2) rough refining using a converter or an electric furnace; (3) refining using a refining furnace + VD or a refining furnace + RH; (4) continuous casting; (5) heating and rolling the continuous casting billet into an intermediate billet; (6) flaw detection and fine repair of the intermediate billet; (7) heating the intermediate billet; (8) controlled rolling and controlled cooling of the intermediate billet; (9) drawing the wire rod in multiple passes to form a steel wire; (10) heat treatment and flaw detection of the steel wire.

5. The method for manufacturing an ultra-high strength spring steel for a hydraulic torque converter for an automobile according to claim 4, characterized in that: The method specifically comprises the following steps: (1) Use molten iron pretreatment to remove sulfur from the molten iron. The sulfur content after molten iron pretreatment is ≤0.005%; (2) Rough refining is carried out by using a converter or electric furnace. The S content of the molten iron entering the rough refining furnace is ≤0.005%, and the content of the five harmful elements in the finished steel is ≤0.0030%. The rough refining furnace controls the oxygen content in the steel and increases the final C content. The P content in the steel is ≤0.012% and the S content is ≤0.005% when the steel is tapped. Alloys are added during tapping to reduce the introduction of harmful elements. (3) After rough refining, the molten steel enters the ladle refining furnace. The basicity of the refining slag in the ladle refining furnace is less than or equal to 1.

4. A vacuum treatment RH or VD furnace is used to remove harmful gases N, H, and O in the steel, so that the N content in the steel is ≤0.0050%, the O content is ≤0.0017%, and the H content is ≤0.0001%; (4) Refining qualified molten steel, ensuring that inclusions fully float, the temperature of the molten steel is suitable for pouring, using protective pouring during pouring, the superheat of the molten steel entering the tundish is ≤25°C, and the cross-sectional dimensions of the steel billet cast by the continuous casting machine are: length 200-500mm, width 200-550mm; (5) The qualified continuous casting billet enters the continuous heating furnace, and the temperature of the billet is controlled to be ≥400℃. According to the calculation summary of the alloy elements and second phase solid solution of this steel grade, the heating temperature is determined to be 1120-1230℃. The cross-sectional dimensions of the rolling intermediate billet are: the length of the square billet is 140mm-220mm, the width is 140mm-220mm, and the diameter of the round billet is 140mm-220mm; (6) After the casting is rolled, magnetic powder or infrared flaw detection is first used to determine the defect location and mark it. The defects at the marked location are ground and cleaned. For the intermediate billet without surface defects, the surface layer within 1-2 mm near the surface is completely removed to remove the decarburized layer on the surface; (7) The intermediate billet with the surface decarburized layer and defects removed enters the heating furnace. In order to control and achieve the target of 11-15 grade austenite grain size of finished steel wire, the heating time should be less than 2 hours and the heating temperature should be 950-1150℃; (8) After the intermediate billet comes out of the heating furnace, high-pressure water dephosphorization is immediately carried out to remove the surface oxide layer and defects during the heating process. According to the thermoplasticity and thermal simulation data of the steel grade, the starting rolling temperature is greater than 890°C, the process rolling temperature is 890-1050°C, the wire laying temperature is 830-900°C, and the cooling rate of the wire rod is 3.0-5.5°C / s; (9) The wire rod is drawn into steel wire in multiple passes, and the wire rod is drawn to the size of the finished steel wire, and the total reduction rate is ≥ 65%; (10) The steel wire needs to be heat treated after drawing. The steel wire is heat treated while being heated, that is, the steel wire is heat treated online. Before the steel wire is coiled, the surface defects are detected by flaw detection equipment. If the depth of the surface defects is greater than 0.1mm, the color code needs to be sprayed.

6. The method for manufacturing an ultra-high strength spring steel for a hydraulic torque converter for an automobile according to claim 5, characterized in that: In step (4), when the continuous casting solid phase ratio is 0.63-0.75, the end is lightly pressed down, and the pressing amount is 2.1-3.6% of the thickness of the ingot, so that the center segregation of the ingot is ≤1.0 level, the center looseness is ≤1.0 level, and the center carbon segregation index is ≤1.3, and finally the deviation of the tensile strength of different pieces of steel wire is ≤50Mpa.

7. The method for manufacturing an ultra-high strength spring steel for a hydraulic torque converter for an automobile according to claim 5, characterized in that: The total heating time is controlled during heating in step (5). The heating time varies according to the billet shape, but the total heating time must ensure that the carbonitride of the microalloying elements is fully integrated into the austenite, that is, the total heating time is 2.5 min / mm-3.5 min / mm, where mm is the cross-sectional size of the billet.

8. The method for manufacturing an ultra-high strength spring steel for a hydraulic torque converter for an automobile according to claim 5, characterized in that: The online heat treatment in step (10) is based on the austenitizing temperature of the steel. The heating temperature before quenching is 860-980°C. The quenching medium is water or oil. When water is used as the quenching medium, the temperature needs to be controlled at 20-50°C. When oil is used, the temperature is ≤40°C. The tempering temperature is selected at 420-500°C according to the requirements of the spring for the tensile strength of the steel wire. The lower the tempering temperature, the higher the tensile strength.